MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN WISATA LOKAL PADA SISWA SMK NEGERI 1 SEYEGAN - Bisri Bisri (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Learning Model "Local Tourism" is a learning model that uses a simple syntax and uses the Local Travel media as objects to provide the initial motivation in students. Each local district must have a tourist area and almost every student must know so that students in learning mathematics will get to learn more tangible media and in accordance with era. Because the study of mathematics by teachers was difficult and unattractive then teachers need to create a lesson plan that could raise the motivation to learn. Response to the students' attitudes is the initial capital to further refinefurther strengthening of knowledge and skills that are expected to get more depth. This is what makes the author feel like trying Learning Model "Local Tourism” to improve students' motivation to learn mathematics SMK Negeri 1 Seyegan, Sleman, Yogyakarta.  Keywords: Learning Model, Local Tourism, Improve, and Motivation